Managerial Short-Termism, Turnover Policy, and the Dynamics of Incentives - Varas, Felipe (Review of Financial Studies, 2018)
I study managerial short-termism in a dynamic model of project development with hidden effort and imperfect observability of quality. The manager can complete the project faster by reducing quality. To preempt this behavior, the prin cipal makes payments contingent on long-term outcomes. I analyze the dynamics of the optimal contract and its implications for the level of managerial turnover. I show that optimal contracts might be stationary and entail no termination. In general, I show that the principal reduces the manager’s temptation to behave myopically by reducing the likelihood of termination and deferring compensation. The model predicts a negative relation between the rate of managerial turnover and the use of deferred compensation that is consistent with evidence of managerial compensation contracts. Received May 23, 2016; editorial decision May 27, 2017 by Editor Francesca Cornelli.